MODEL-MODEL PEMBELAJARAN YANG UMUM DIGUNAKAN - Mubarok, Frenky (Prodi PIAUD IAI Pangeran Dharma Kusuma Indramayu, 2019)
A learning model is a framework that helps educators design and implement effective teaching and learning processes. Various learning models, such as traditional, active, differentiated, integrated, technology-based and social-emotional models, have their own characteristics, advantages and disadvantages. Choosing the right model depends on the students' needs, learning objectives and educational context. Each student is unique in the way they learn, so teachers are required to be dynamic and flexible in applying learning models in the classroom. This flexibility allows teachers to combine various models to create an inclusive, effective and fun learning environment. Adaptive approaches not only help students understand the material more deeply but also encourage the development of their individual character and potential. This article examines various learning models and highlights the importance of teachers' dynamic attitude in adapting models to students' needs in order to achieve optimal educational goals.